Temperature shocks and their effect on the price of agricultural products: Panel data evidence from vegetables in Mexico - Jesus Arellano Gonzalez; Miriam Juarez-Torres; Francisco Zazueta Borboa (Banco de México, 2023)
In this paper, we estimate the effect of temperature shocks on the price of nine vegetables with a high contribution to Mexico's non core inflation. We utilize monthly panel data of the price index of each vegetable at the city level which we combine with high resolution weather data of the producing states. For every city, we construct a relevant temperature measure by weighting the different temperatures of its supplier states using historic production shares and distance. Our findings elicit a convex U-shaped relationship between temperature and vegetable prices and a high sensitivity of the latter to contemporaneous and lagged temperature shocks that occur within their growing period. Our findings also suggest that temperature shocks may have a detrimental effect on vegetable yields which may be an important driver of the impact on prices.
Keywords: E31; Q15; Q54; 330; Food Inflation; Weather Shocks; Vegetable Prices; Local Markets